Functions of the Medieval Parliament of England. - Sayles, G. O. (Continuum International Pub. Group, 1987)
This series of documents, covering the first hundred years after the Provisions of Oxford in 1258, is given in translation so that all who are interested in the history of parliament but have little Latin and less Old French may consult them.